Development Content Learning System in Acid Base Solution Using Flipped Classroom at Senior High School - Elvina Gusman; Fadila Gusman; Wirasyid Hafizul Lathief (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2021)
This research was conducted on developing an e-learning content using the Flipped Classroom application in chemistry subjects which is Acid base solution. The method of this research applied Research and Development (R and D) that use the 4-D model with the stages of define, design, d evelop and disseminate. In designing this research, the author applied Thiagarajan (4D) model. In this model, 4D means define, design, develop, and disseminate. Populations in this research are students from Senior High School in West Sumatera, Indonesia. There are 10 students of SMA N 1 Rambatan, in 11 class level as respondents for developing this product.The data sources of this study were 3 chemistry and student and teacher in Rambatan. This study applied content validity questioner as an instrument. were a content validity questionnaire, construct validity and a practicality questionnaire. This research focus on the develop stage. To analyses the data, the 4D technique is used to process the numbers of questionnaire that have been obtained from the measurement results of the questionnaire data obtained from calculations using the Aiken's V formula and a Likert scale.. The data analysis results show that the mean of Aiken's V formula and a Likert scale of content validity is 0.832 and construct validity is 0.847 with high and very high validity categories.